Book Review: Clarke, D. 2012: Africa's Future: Darkness to Destiny. (January 2017) - Ojanperä, Sanna
Clarke, D. 2012: Africa's Future: Darkness to Destiny . London: Profile Books. 305 pp. £14.99. ISBN: 978-1-846-68570-5 (paperback). £14.99 ISBN: 978-1-847-65 799-2 (e-book).